Encavalgamento poético e pistas prosódicas do limite final do enunciado fonológico a partir da análise das Cantigas de Santa Maria (Século XIII) (Poetic enjambment and phonological clues for the phonological utterance final boundary, from the analysis of) - Massini-Cagliari, Gladis (2023)
This paper objectives to analyse the relation between lyrics and music in the Cantigas de Santa Maria, searching for clues in the musical notation to the final boundary of the phonological utterance, as a linguistic prosodic constituent, considering the occurrence of poetic enjambments. This research shows that the poetic enjambment does not interfere in the division of the cantigas in phonological utterances, in the prosodic level, and that the main musical correlate to Us final boundaries is the coincidence between the prominent syllable in the U and the initial beat, which is prominent, in the musical level.